Feasibility Study, Carrying Capacity and Ecotourism Activities in the Blekok Village Mangrove Area of Situbondo Regency - Insani, Nailul; Wirahayu, Yuswanti Ariani; Arif, Dian Adhetya; Sabilau, Oldheva Genisa (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Blekok Village is one of the mangrove areas that was developed as conservation-based ecotourism by the Situbondo Regency Government since 2017. The Blekok village is located in Pesisir Hamlet, Klatakan Village, Kendit District, Situbondo Regency. This area has been designated as a mangrove area inhabited by water birds of the type Ardeidae called birds blekok by the surrounding community. Over time Blekok village has been increasingly crowded by tourists both inside and outside the country. The mangrove ecotourism area was developed as an appropriate form of management to ensure the sustainability of conservation and rehabilitation while at the same time encouraging the economy of local communities.The aim of this research are to calculate the tourist suitability index, calculate the carrying capacity of the region and identify ecotourism activities that can be carried out in the mangrove area of Kampung Blekok. The methods used in this study are qualitative and quantitative. Tourism suitability assessment uses the Regional Suitability Index (IKW), calculation of Regional Carrying Capacity and identification of ecotourism activities carried out with a 4A assessment (Attraction, Amenity, Accessibility, Ancilliary). Data collection uses visual observation techniques, interviews and documentation.The results showed that the mangrove area of Kampung Blekok Situbondo Regency was suitabel for mangrove tourism activities with a suitability value of 82,05%. The area that can be utilized for ecotourism covers 6.471,9 and the carrying capacity of the area for tourism activities is 648 people / day (open 10 hours/day). For the types of tourism activities that can be carried out in the mangrove ecotourism area totaling 8 activities, they are photography (photography), mangrove tracking, bird watching, observation tower, observation of mangrove (education), nursery of mangrove, boat tourism (boating) and enjoy the atmosphere of the sunset.